2012
DOI: 10.1080/09064710.2012.682734
|View full text |Cite
|
Sign up to set email alerts
|

Root distribution patterns of white yam (Dioscorea rotundataPoir.): a field study

Abstract: The productivity of white yam (Dioscorea rotundata Poir) must increase to sustainably meet the demand of the increasing populations in the developing world where this is a staple crop. Although this could be achieved through the use of mineral fertilizers, reports indicate limited effects of these inputs on tuber yield. We hypothesized (i) that D. rotundata has a small and shallow root system and (ii) that this root system does not respond to mineral fertilizer application. Two field experiments were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Recent studies in sweetpotato indicate direct influence on RSA of spatial and temporal availability of water and N availability similar to model systems (Villordon et al, 2014a). In yam, Hgaza et al (2012) found no fertilizer response of tuber yield but a positive correlation between thinner, longer roots with tuber yield.…”
Section: The Relationship Between Root System Architecture and Abiotimentioning
confidence: 80%
See 1 more Smart Citation
“…Recent studies in sweetpotato indicate direct influence on RSA of spatial and temporal availability of water and N availability similar to model systems (Villordon et al, 2014a). In yam, Hgaza et al (2012) found no fertilizer response of tuber yield but a positive correlation between thinner, longer roots with tuber yield.…”
Section: The Relationship Between Root System Architecture and Abiotimentioning
confidence: 80%
“…Only one reference was found for yams, the second most important root crop in Sub-Saharan Africa 1 , which described two distinct well-organized root systems: the seminal root system and the adventitious, more definitive root system (Charles-Dominique et al, 2009). Other studies in yam only focused on root morphology at crop harvest stage in response to fertilization (Melteras et al, 2008; O’Sullivan, 2008; Hgaza et al, 2012). Iwama et al (1977) specifically analyzed root systems and the relationship between root systems and tuber yield in potato (Iwama et al, 1981).…”
Section: Root System Architecture In Root and Tuber Cropsmentioning
confidence: 99%
“…In addition, leaf thinning might also depress root growth (Hodgkinson & Becking, 1978). Although the relationship between root growth and tuber yield was not clear in white Guinea yam (Hgaza et al, 2012), Villordon et al (2014) indicated that lateral root development is related to yield formation in tuber crops. These results suggest that leaf thinning after the onset of tuber growth should be avoided and thinning at an earlier growth stage is preferable.…”
Section: Discussionmentioning
confidence: 99%
“…Charles-Dominique et al (2009) concluded the importance of studying the yam root system architecture as a whole and simultaneously in order to understand its growth, development and tuber formation. In a similar study, Hgaza et al (2012) documented the response of the RSA of water yam ( Dioscorea alata ) and white yam ( Dioscorea cayennensis subsp. rotundata ) to mineral fertilizer application under field conditions.…”
Section: Root Architecture and Nutrient Efficiency In Root And Tuber mentioning
confidence: 99%
“…Results revealed three root types (seminal, adventitious and tuber roots) and differences in root length density, root mass density and specific root length correlated directly with higher temperature and not with fertilizer application when compared to controls. Hgaza et al (2012) concluded that tuber formation was independent from seminal and adventitious root development and mineral nutrition did not affect final tuber yield.…”
Section: Root Architecture and Nutrient Efficiency In Root And Tuber mentioning
confidence: 99%